Mother’s Expressions of Love and the Existing Consequences in Malaikat Juga Tahu and Tidur - Nadia Anggie Wijaya (Institute of Research and Community Outreach - Petra Christian University, 2019)
Short story is a type of popular literature in Indonesia. In short stories, love is one of the most well-known topics for the Indonesian audience. Amongst various types of love, a mother’s love is talked about the most. Thus, I decide to analyze how mothers express their love for their children in a compilation book titled Rectoverso. Also, I discover the consequences that the mothers experience due to their choices regarding love. By using the theory of love and the concept of motherly love from the book “The Art of Loving” by Erich Fromm, I find that the mothers have to face several choices that can give impacts toward their children and themselves. Every decision they make is caused by their love toward their children. Furthermore, the mothers prioritize their children instead of themselves. The impacts they experience may be positive or negative, depending on the situation. Keywords: short story, love, mothers, motherly love